Association of Cystatin C-Based Glomerular Filtration Rate with SYNTAX Score in Patients with Diabetes - Yan, L. Q.; Cao, X. F.; Zheng, Y.; Guo, N.; Zhao, R. C.; Yu, J.; Han, J.; Han, L. X. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Serum cystatin C has been proposed as a better marker of glomerular filtration rate than serum creatinine. SYNTAX score (SXscore) can accurately reflect the severity of coronary artery disease (CAD). However, the association between Cystatin C-based glomerular filtration rate (eGFRcys) and SXscore in patients with diabetes has never been reported.We prospectively included 656 consecutive patients with diabetes who were angiographically diagnosed with CAD from January 2010 to December 2011. Renal function was assessed by eGFRcys. SXscore was calculated using SXscore algorithm. Ordinal logistic regression and Pearson correlation were used to analyze the association between eGFRcys and SXscore.Patients with renal dysfunction were older, more often female, more likely to have a history of hypertension and less tobacco use when compared with those patients with normal renal function. Age, sex, SBP, DBP, fasting glucose, HbA1c, TC, LDL, HDL, TG, BMI and CRP were not different among SXscore tertile groups. Incidence of hypertension, hyperlipidemia, family history and tobacco use were similar among these groups. Correlation analysis suggested that eGFRcys was negatively correlated with SXscore (R=−0.255, P<0.001). Ordinal logistic regression showed that eGFRcys was an independent predictor of SXscore (β=−0.027, P<0.001).eGFRcys was an independent predictor of SXscore in patients with diabetes. This might help explain the increased risk of CVD events and mortality in patients with renal dysfunction. Further prospectively multiple centre studies are required to better quantify this finding.
Keywords: glomerular filtration rate; cystatin C; chronic kidney disease; coronary artery disease; SYNTAX score; diabetes